A closing call's impact on market quality: evidence from Abu Dhabi stock exchange. Issue 1 (2nd January 2020) - Orhun, Eda
Abstract : Purpose: This paper aims to look at the effects of the closing call auction on market quality and behavior by using the natural experiment of its introduction at the Abu Dhabi Stock Exchange. Design/methodology/approach: Current paper studies the effect of closing call auction on various market quality factors such as liquidity, bid-ask spreads, volatility and market efficiency. Liquidity is proxied by trading volume. Bid-ask spreads provide a measure for the cost of trading in the market. Volatility is measured by using Parkinson's (1980) volatility as in Huang and Tsai (2008). Last but not least, efficiency will be obtained by estimating a relative return dispersion measure as in Huang and Tsai (2008). Findings: The introduction of the closing call auction leads to a significant decrease in the trading volume toward the end of the continuous trading. At the same time, trading activity taking place during the call auction significantly increases. This implies a redistribution of liquidity. The implementation of the closing call auction also improves market quality by reducing market inefficiency in terms of firm-specific noise. The study also documents that there exists no significant change in the cost of trading and intraday volatility in the post-period following the adoption of closing call auction. Originality/value: This current study is the first one looking at this topic for the Abu Dhabi Stock Exchange. Specifically, this paper looks at the changes in trading volume, bid-ask spreads, intraday return volatility and market efficiency after the implementation of the closing call mechanism.